2016
DOI: 10.1080/14681994.2016.1228871
|View full text |Cite
|
Sign up to set email alerts
|

The effects of radical prostatectomy on gay and bisexual men's mental health, sexual identity and relationships: qualitative results from the restore study

Abstract: The effect of prostate cancer treatment in gay and bisexual men is an under-researched area. In 2015, we conducted in-depth telephone interviews with 19 gay and bisexual men who had undergone radical prostatectomies. Across the respondents’ five emotional themes emerged: (1) shock at the diagnosis, (2) a reactive, self-reported “depression”, (3) sex-specific situational anxiety, (4) a sense of grief, and, (5) an enduring loss of sexual confidence. Identity challenges included loss of a sense of maleness and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 36 publications
0
62
0
Order By: Relevance
“…We identified 14 studies that characterized the mental health impact and degree of adjustment to cancer . In 1 large survey study of individuals with a history of cancer that compared SGM with propensity score‐adjusted heterosexual peers, SGM survivors reported higher rates of depression and relationship difficulty .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 14 studies that characterized the mental health impact and degree of adjustment to cancer . In 1 large survey study of individuals with a history of cancer that compared SGM with propensity score‐adjusted heterosexual peers, SGM survivors reported higher rates of depression and relationship difficulty .…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies in the review focused explicitly on sexual functioning among SGM survivors or included satisfaction and/or adjustment to sexual functioning after cancer . One study of the impact of cancer on sexual performance in SGM couples found that pain and other symptoms of cancer were associated with impaired sexual functioning, including a decrease in arousal and desire .…”
Section: Resultsmentioning
confidence: 99%
“…GBQ men identify the prostate as a sexual organ that is directly related to sexual pleasure (Filiault, Drummond, & Smith, ; Rosser et al, ; Ussher et al, ; Ussher, Perz et al, ; Ussher, Perz, Rose, Kellett, & Dowsett, ). For example, in one of the articles that reported on a qualitative study, a GBQ man said that “[The prostate] is a very sensitive part of a man's body, and it is a great part of the enjoyment of anal sex” (Ussher, Perz et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Adverse effects that directly affect sexuality post‐treatment are loss of libido, urinary and bowel incontinence, anal irritation and discomfort, erectile dysfunction, decreased penile size, and ejaculation and orgasmic dysfunction (Lee et al, ; McConkey & Holborn, ; Torbit, Albiani, Crangle, Latini, & Hart, ; Ussher et al, ; Ussher, Perz et al, ). These adverse effects have a profound, often permanent and unanticipated impact on GBQ men's sexual practices (Rosser et al, ). This quote exemplifies the impact:
If you have any chance of going home with somebody, if you want to leave and do that, you can’t drink a lot beforehand because you don’t want to pee in the guy’s bed.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation